PENGARUH PROFESIONALISME KERJA, KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA DINAS KESEHATAN PROVINSI MALUKU - Lalihatu, Gloria; Pentury, Gerrit; Rehatta, Pieter (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2024)
The purpose of the study was to determine the effect of Work Professionalism, Competence and Non-Physical Work Environment simultaneously on the performance of employees of the Maluku Provincial Health Office. The population in this study amounted to 116. Determination of the number of samples using probality random sampling techniques with the Slovin formula obtained 54 respondents, the analytical test tool used was SPSS 24. Data processing techniques carried out using quantitative methods with descriptive analysis. The results of this study indicate that Work Professionalism has a negative and significant effect on employee performance, while Competence and Non-Physical Work Environment have a positive and significant effect on employee performance.